Protective effects of pitanga leaf extract on oxidative stress and hepatic-testicular alterations in a rat model of metabolic syndrome - Evy Sulistyoningrum; Asri Hendrawati; Mutia Fudhla Karima (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
The prevalence of metabolic syndrome (MetS) is increasing. Oxidative stress is a major consequence of MetS and can affect multiple organs, including the liver and testes. Pitanga leaves possess potent antioxidant and anti-inflammatory properties and are rich in anthocyanins, phenolic acids, and flavonoids, which may provide protection against oxidative damage. This study evaluated the effects of pitanga leaf extract on oxidative stress markers and liver and testicular histology in a rat model of MetS. Twenty-five male Wistar rats were randomly assigned to five groups: normal, MetS, MetS + telmisartan (8 mg/kg), MetS + pitanga leaf extract (PLE) 50 mg/kg), and MetS + PLE (100 mg/kg). MetS was induced for eight weeks using a high-fat diet, and 20% fructose was administered concurrently with the interventions. Plasma oxidative stress markers were assessed on day 57, after which the tissues were collected for histological examination. Administration of PLE at 50 and 100 mg/kg reduced plasma malondialdehyde levels and increased glutathione peroxidase levels (p < 0.05). It also improved liver and testicular indices (p < 0.05) and reduced hepatic steatosis. In conclusion, pitanga leaf extract ameliorated oxidative stress and liver and testicular damage in rats with MetS, although its testicular effect was limited to reducing the testicular index.